Immune and vascular modulation by HERVs: the role of CXCR1 and IL18RAP in dengue severity progression - Ferreira, Cristina Santos; Da Silva, Alan Tardin; Brustolini, Otávio José Bernandes; Soares, Beatriz Rodrigues Pellegrina; Manuli, Erika Regina; Ramundo, Mariana Severo; Paranhos-Baccala, Glaucia; Sabino, Ester Cerdeira; Vasconcelos, Ana Tereza Ribeiro (Frontiers in Immunology, 2025)
IntroductionHuman Endogenous Retroviruses (HERVs), which can be activated by viral infections, have complex roles in gene regulation and immune modulation. However, their contribution to disease progression is not yet fully understood. Dengue fever ranges from mild symptoms to severe cases characterized by plasma leakage and immune dysregulation, providing a relevant context to investigate these interactions.MethodsThis study comes up with a comprehensive analysis of differentially expressed HERVs (DE-HERVs), protein-coding genes (DEGs), and regulatory elements such as microRNAs (DE-miRNA) and non-LTR retroviruses (DE-LINEs and DE-SINEs) derived from the transcriptomes of Brazilian dengue patients across different disease stages.ResultsThe results show that DE-HERVs are associated with key genes identified in severe dengue cases, including ARG1, SLC15A2, COL3A1, SVEP1, CH25H, CST7, CXCR1, IL18RAP, SORL1, and TACR1, suggesting their role in immune modulation and endothelial permeability. Specifically, the upregulation of CXCR1 and IL18RAP genes in patients who progressed to severe dengue correlates with a complex regulatory network involving down-regulated microRNAs (miRNAs) and non-LTR retroviruses, emphasizing their relevance to inflammation and vascular permeability. MicroRNAs and non-LTR retroviruses were found to regulate these genes differently across dengue stages, with non-LTR elements appearing predominantly in non-severe cases and miRNA expression profiles varying across the comparison groups.DiscussionThese findings improve our understanding of the molecular mechanisms underlying dengue progression and suggest that HERV-related regulatory networks may influence viral infections. Further research is required to clarify the specific roles of HERVs in dengue pathogenesis.